Russian Wives in America: A Sketchy Portrait - Ryabov, Igor (Qualitative Sociology Review, 2013)
As more and more people around the globe join the transnational marriage market, marriage is becoming an increasingly global affair. Yet, transnational marriage migration has not received the scholarly attention it deserves. The present study is focused on post-migration experiences of twenty female marriage migrants from the former Soviet Union married to the U.S. nationals and lawful permanent residents. Through participant observation, the present study investigates the issues related to transnational partner choice and immigrant adjustment of these women. While the majority of informants identified the lack of local marriageable men as the major push factor, women tended to differ significantly with respect to the factors important for their choice of partner. While some stressed the importance of ethnicity and race of their spouse, others did not. The most important finding is that, in order to legitimize their marriage and resist gender oppression both in the domestic and public domains, women produced discourses shaped by the mainstream gender ideology that stigmatizes transnational marriage migrants.